PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPE STAD BERBANTUAN MEDIA AUDIO VISUAL TERHADAP HASIL BELAJAR IPA SISWA KELAS III SD NEGERI 42 PEKANBARU - Oktarianda, Ranty; Alpusari, Mahmud; Noviana, Eddy (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: This research is motivated by the teacher who still uses the teaching method with the old method and the difficulty of the students to understand the abstract science learning, thus causing the low value of the students' science. Implementation of STAD cooperative learning method using media audio visual is expected to be influential improving science achivements. This research uses quasi experimental method with nonequivalent control group design. The purpose of this study is to determine the effect of STAD cooperative learning method using media audio visual to the students' science achivements in the experimental class and to know the difference in the increase of students' science achivements between experimental and control classes. This research was conducted at SD Negeri 42 Pekanbaru with class III D as control class and class III E as experiment class. The research shows that there is an influence of STAD cooperative learning method using media audio visual and difference in the improvement of students' science achivements between the experimental and control class. In the experimental class there is an increase learning with average gain of 0.328 medium category. While the control class increased learning average gain of 0.086 low category. This research, there is influence of STAD cooperative learning method using media audio visual to students' learning result at experimental class with value (r) 0,701 with strong relation and coefficient determination () 49,10% STAD cooperative learning method using media audio visual, while 50,90% was influenced by other factors. Thus, STAD cooperative learning method using media audio visual influence on science learning results of students with improved learning outcomes than the application of lecture methods.Key Word: STAD, Audio Visual Media, Science Achivements